2010
DOI: 10.1111/j.1365-2133.2010.10055.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cytokine secretion from lymphocytes of patients with hypersensitivity reactions to contaminated heparins

Abstract: The in vitro lymphocyte reactivity pattern of PBMC from individuals with hypersensitivity reactions to contaminated heparins was neither typical for an immune-mediated nor for a nonimmune-mediated reaction. Possible effects of heparins in the test system itself may require consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…B. Proliferation der Lymphozyten oder freigesetzte Cytokine [48,49] zur Verfügung. Vor allem der ELISpot-Assay hat eine zunehmende Bedeutung in den letzten Jahren gewonnen.…”
Section: In-vitro-testunclassified
“…B. Proliferation der Lymphozyten oder freigesetzte Cytokine [48,49] zur Verfügung. Vor allem der ELISpot-Assay hat eine zunehmende Bedeutung in den letzten Jahren gewonnen.…”
Section: In-vitro-testunclassified
“…288 Darby and coworkers 287 reported that the majority of HIV-infected hemophilia patients had hemophilia A. Considering the recent interest in adverse reactions secondary to heparin use, 316,317 there is a need for another comprehensive conference on heparin. 289,290 In addition, the problems with the thrombogenicity of PCCs 291,292 led to the development of highly purified plasma-derived factor IX products.…”
Section: Vitamin K-dependent Proteinsmentioning
confidence: 99%